OGRANICZENIA AUTORSKICH PRAW MAJĄTKOWYCH DO PROGRAMÓW KOMPUTEROWYCH - Kępiński, Jakub (Wydział Prawa i Administracji UAM, 2007)
Copyright law is the area o f intellectual property law that regulates the creation and use of a range of cultural goods such as books, songs, films and computer programmes. The paper focuses on the protection o f computer programmes, and, in particular, on the rights of their lawful users, such as buyers and licensees in Poland. The Polish regulation is based on the Council Directive o f 14 May 1991 on the legal protection of computer programmes (91/250/EEC) which was introduced to the Copyright Law during the process of harmonization of the Polish Law with the European Law (Dz. U. from 2006, No 90, item 631). The paper is divided into four parts which reflect the rights o f a legal user. The first part presents the right to use the computer programme in accordance with its intended purpose, including the correction of errors. The second part explains the right to make a back-up copy. The third one focuses on the right to observe, study or test the functioning of the programme in order to determine the ideas and principles which underlie its elements. Finally, the fourth part deals with the right of decompilation. The intention o f the author was to write an exhaustive paper that would explain the rights of a lawful user. Until now the majority o f articles and monographs have focused on the protection of computer programmes from the point o f view o f their authors.
THE RIGHTS OF LAWFUL USERS OF COMPUTER PROGRAMMES